Visuomotor Correction is a Robust Contributor to Force Variability During Index Finger Abduction by Older Adults - Tracy, Brian L.; Hitchcock, Leah N.; Welsh, Seth J.; Paxton, Roger J.; Feldman-Kothe, Caitlin E. (Frontiers in Aging Neuroscience, 2015)
We examined aging-related differences in the contribution of visuomotor correction to force fluctuations during index finger abduction via the analysis of two datasets from similar subjects. Study (1) Young (N = 27, 23 ± 8 years) and older adults (N = 14, 72 ± 9 years) underwent assessment of maximum voluntary contraction force (MVC) and force steadiness during constant-force (CF) index finger abduction (2.5, 30, 65% MVC). For each trial, visual feedback of the force (VIS) was provided for 8–10 s and removed for 8–10 s (NOVIS). Visual gain of the force feedback at 2.5% MVC was high; 12- and 26-fold greater than the 30 and 65% MVC targets. Mean force, standard deviation (SD) of force, and coefficient of variation (CV) of force was calculated for detrended (<0.5 Hz drift removed) VIS and NOVIS data segments. Study (2) A similar group of 14 older adults performed discrete, randomly-ordered VIS or NOVIS trials at low target forces (1–3% MVC) and high visual gain. Study (1) For young adults the CV of force was similar between VIS and NOVIS for the 2.5% (4.8 vs. 4.3%), 30% (3.2 vs. 3.2%) and 65% (3.5 vs. 4.2%) target forces. In contrast, for older adults the CV of force was greater for VIS than NOVIS for 2.5% MVC (6.6 vs. 4.2%, p < 0.001), but not for the 30% (2.4 vs. 2.4%) and 65% (3.1 vs. 3.3%) target forces. At 2.5% MVC, the increase in CV of force for VIS compared with NOVIS was significantly greater (age × visual condition p = 0.008) for older than young adults. Study (2) Similarly, for older adults performing discrete, randomly ordered trials the CV of force was greater for VIS than NOVIS (6.04 vs. 3.81%, p = 0.01). When visual force feedback was a dominant source of information at low forces, normalized force variability was 58% greater for older adults, but only 11% greater for young adults. The significant effect of visual feedback for older adults was not dependent on the order of presentation of visual conditions. The results indicate that impaired processing of visuomotor information underlies the greater motor variability observed in older adults during lab-based isometric contractions of a hand muscle.